2008
DOI: 10.1136/ard.2008.100503
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosing spondylitis and the risk of fracture: results from a large primary care-based nested case-control study

Abstract: Patients with AS have an increased risk of clinical vertebral fracture but not of non-vertebral fractures, while the risk of any clinical fracture is increased in patients with concomitant inflammatory bowel disease. The mechanism by which non-steroidal anti-inflammatory drugs reduce the risk of any clinical fracture warrants further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
104
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(122 citation statements)
references
References 26 publications
8
104
1
9
Order By: Relevance
“…[5,3] In general, AS is associated with bone loss in the vertebrae and an increased prevalence of vertebral fractures. [6,7] Cooper et al [6] identified markedly increased relative risk of vertebral morphometric deformities in patients with AS compared with the control population. The review of recent literature on osteoporosis and vertebral fractures in AS published by DaveyÀRanasinghe and Deodhar [8] suggests that the prevalence of osteoporosis in AS patients is 25% and that of vertebral fractures is 10%.…”
Section: Introductionmentioning
confidence: 99%
“…[5,3] In general, AS is associated with bone loss in the vertebrae and an increased prevalence of vertebral fractures. [6,7] Cooper et al [6] identified markedly increased relative risk of vertebral morphometric deformities in patients with AS compared with the control population. The review of recent literature on osteoporosis and vertebral fractures in AS published by DaveyÀRanasinghe and Deodhar [8] suggests that the prevalence of osteoporosis in AS patients is 25% and that of vertebral fractures is 10%.…”
Section: Introductionmentioning
confidence: 99%
“…1 It has been hypothesized that, in common with other chronic inflammatory arthritides such as rheumatoid arthritis and spondyloarthropathy, 2,3 gout may be associated with an increased risk of fracture, primarily owing to the negative effects of chronic inflammation on bone, because proinflammatory cytokines are known to induce bone loss. However, the effects of serum urate on bone health are still under debate 4,5 and previous studies that have assessed the impact of gout and urate-lowering therapy on fracture risk have provided conflicting results.…”
mentioning
confidence: 99%
“…The increased risk is more strongly related to daily dose than to the cumulative dose with a monotonic relationship [48]. Several early studies documented an increased fracture risk in subjects with rheumatoid [61][62][63] and psoriatic arthritis [64], ankylosing spondyloarthritis [65][66] and in general with any connective tissue disease. Relative risks associated with each CRF described above and used in the model are reported in Table VII.…”
Section: Clinical Risk Factorsmentioning
confidence: 99%